1995
DOI: 10.1111/j.1600-0420.1995.tb00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperglycemia duration on rabbit corneal thickness and endothelial ATPase activity

Abstract: This study compares corneal thickness and corneal endothelial Na,K ATPase activity in normal and age-matched diabetic rabbits with up to 10 weeks of hyperglycemia. Corneal endothelial Na,K ATPase activity in normal rabbits increased between 10 and 20 weeks of age. Corneal thickness increased after 5 weeks of hyperglycemia. Decreased corneal endothelial homogenate Na,K ATPase activity was first seen after 10 weeks of hyperglycemia, though an earlier onset was possible due to sampling restrictions. Corneal endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Diabetes is known to impair corneal endothelial function. It has been shown that Na + /K + -ATPase activity is reduced in diabetic rats [11] . Since this enzyme is the main component of the endothelial pump, impairment of the activity of the enzyme leads to a decreased corneal swelling response and slower recovery from hypoxic edema in diabetics compared to nondiabetics [10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is known to impair corneal endothelial function. It has been shown that Na + /K + -ATPase activity is reduced in diabetic rats [11] . Since this enzyme is the main component of the endothelial pump, impairment of the activity of the enzyme leads to a decreased corneal swelling response and slower recovery from hypoxic edema in diabetics compared to nondiabetics [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is associated with corneal structural and functional alterations [10,11] . The effect of exposure to HBO treatment on CCT in diabetic subjects is not known.…”
Section: Introductionmentioning
confidence: 99%
“…16 -19 The Na ϩ -/K ϩ -dependent ATPase (Na,K-ATPase), expressed in the basolateral membrane of corneal endothelial cells, is primarily responsible for the pump function of the corneal endothelium. 20 Herse and Adams 21,22 have shown that functional abnormalities, such as increased corneal thickness and decreased ability to recover from corneal edema in alloxaninduced diabetic rabbits, are associated with decreased Na,K-ATPase activity in the corneal endothelium. Whikehart et al 23 have reported that elevated glucose levels reduce Na,K-ATPase activity in cultured bovine corneal endothelial cells.…”
mentioning
confidence: 99%
“…The role of hyperglycemia on corneal thickness and endothelial and epithelium function has been clearly documented. [46][47][48][49] However, there are also enough data for demonstration of the importance of hyperglycemia control on the cornea. 50,51 For these reasons, we believe that some of the beneficial effects of…”
Section: Discussionmentioning
confidence: 99%